Association of hypoxia-inducible factors 1alpha and 2alpha with activated angiogenic pathways and prognosis in patients with endometrial carcinoma. - Sivridis, E; Giatromanolaki, A; Gatter, K; Harris, A; Koukourakis, M (2002)
BACKGROUND: Hypoxia-inducible factor 1alpha (HIF-1alpha) and HIF-2alpha are essential regulatory proteins for the adaptation of tumor cells to hypoxia, and they stimulate angiogenesis through activation of the vascular endothelial growth factor (VEGF) gene. METHODS: HIF-1alpha and HIF-2alpha proteins were studied immunohistochemically in a group of 81 patients with Stage I endometrial adenocarcinoma of the endometrioid cell type. The results were correlated with intratumoral angiogenesis, the expression of the angiogenic factors VEGF and thymidine phosphorylase (TP), and the VEGF/receptor (VEGF/KDR) complex. Relations also were sought with estrogen receptor (ER) and progesterone receptor (PR), with the apoptosis-related proteins bcl-2 and p53, with several histopathologic parameters, and with patient prognosis. In addition, a sample of 25 normal endometria at various phases of the menstrual cycle was studied for the presence of HIF-1alpha and HIF-2alpha. RESULTS: HIF-1alpha expression was detected in 49% of endometrial carcinomas. The expression was cytoplasmic or mixed nuclear/cytoplasmic. HIF-1alpha expression was associated with up-regulation of the VEGF pathway and with increased standard microvessel density (sMVD) and activated VEGF/KDR microvessel density (aMVD). It also was associated with a poor prognosis in both univariate and multivariate analyses. HIF-2alpha protein showed a pattern of expression similar to the pattern seen in HIF-1alpha, but expression of HIF-2alpha protein occurred in only 17% of endometrial carcinomas, and it was associated with increased TP reactivity. There also was a relation of HIF-1alpha expression with well-differentiated endometrial neoplasms, and there was a marginal association of HIF-1alpha and HIF-2alpha with ER expression. With reference to normally cycling tissues, HIF-1alpha nuclear/cytoplasmic expression was particularly strong in the samples of early proliferative phase endometrium compared with HIF-2alpha protein expression, which showed a constant reaction throughout the menstrual cycle. CONCLUSIONS: The up-regulation of HIF-1alpha and, to a lesser extent, of HIF-2alpha is a common event in Stage I endometrial adenocarcinomas. In these tumors, HIF-1alpha expression is related to increased angiogenesis, through activation of the VEGF angiogenic pathway, and to an unfavorable prognosis. HIF-2alpha accumulation is associated with increased expression of the angiogenic factor TP.